Bearing-Only Adaptive Formation Control Using Back-Stepping Method - Li, Sulong; Wang, Qin; Wang, Enci; Chen, Yangyang (Frontiers in Control Engineering, 2021)
In this paper, the bearing-only formation control problem of a class of second-order system with unknown disturbance is investigated, where the control law merely depends on the relative bearings between neighboring agents. In order to offset the effect of unknown disturbance on the system, adaptive estimation is introduced. In the design of the control law, the back-stepping design method and the negative gradient method are used. The Barbalat's Lemma is used to prove the global stability of the system. The simulation results prove the effectiveness of the proposed formation control algorithm.